Termite Species Diversity In Oil Palm Plantations In Dharmasraya District, The Province Of West Sumatra - Heriza, Sri (Jurusan Budidaya Perkebunan, 2023)
Termite are pests that often attack oil palm plantations. Information on the diversity of termite species that attack oil palm plants is needed in an effort to save oil palm yields. The method in this study used an observation plot measuring 50 m x 10 m. One observation plot was divided into observation sub-plots with a size of 5 m x 5 m in order to obtain 20 observation sub-plots. Each observation plot was carried out in eleven sub-districts in Dharmasraya Regency. Termite samples in each observation plot were identified in the laboratory. Every termite found in the observation sub-plot was collected. The termites collected were from the caste of soldiers and workers. The termites were put into a collection bottle containing 70% alcohol and labeled, then identified descriptively by observing the characteristics of the termites including the shape and size of the head, mandible, and the antenna segments of the soldier caste. Identification was carried out using a Leica M205 C microscope and photographed with a Leica DFC450 camera. In this study there are 8 species of termites found viz Coptotermes curvignathus, Schedorhinotermes longirostris, Schedorhinotermes javanicus, Heterotermes indicola, Globitermes globosus, Dicuspiditermes nemorosus, Pericapritermes mohri, Macrotermes gilvus.